WOMEN’S LEADERSHIP RESILIENCE IN PATRIARCHAL ORGANISATIONS: A STUDY OF THE REGIONAL LEADERSHIP COUNCIL OF PEMUDA PANCASILA, SOUTH SULAWESI - Cici Andi Masnur Azhary; Muhammad; Gustiana A. Kambo (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
This study examines women’s leadership in a masculine organizational context to analyze how gender interacts with institutional structures, social norms, and power relations. It aims to explain how leadership legitimacy is constructed through performative practices and collaborative strategies. The research employs a qualitative case study approach, utilizing in-depth interviews, document analysis, and interpretive analysis grounded in gender politics theory, performativity, and organizational resilience frameworks. The findings reveal that leadership legitimacy is not derived solely from formal authority but is produced through repeated performative acts, redistribution of authority, collaborative decision-making, and symbolic negotiation within patriarchal structures. Women leaders strategically combine assertiveness and relational competence to navigate role incongruity and double bind dynamics. Collaborative leadership practices shift power relations from hierarchical domination to relational interdependence, while collective voice mechanisms institutionalize deliberation as an organizational norm. The study also demonstrates that symbolic resources, social networks, and adaptive identity work strengthen organizational resilience and legitimacy in non-state institutions. This study contributes to gender politics scholarship by integrating performativity theory, social psychological leadership research, and organizational resilience into a contextualized analysis of women’s leadership. It highlights the importance of relational, adaptive, and transformative practices in reshaping power structures and suggests future comparative and multi-level research across diverse institutional settings.